2003
DOI: 10.1073/pnas.0530202100
|View full text |Cite
|
Sign up to set email alerts
|

Essential function of α-calcium/calmodulin-dependent protein kinase II in neurotransmitter release at a glutamatergic central synapse

Abstract: A significant fraction of the total calcium͞calmodulin-dependent protein kinase II (CaMKII) activity in neurons is associated with synaptic connections and is present in nerve terminals, thus suggesting a role for CaMKII in neurotransmitter release. To determine whether CaMKII regulates neurotransmitter release, we generated and analyzed knockout mice in which the dominant ␣-isoform of CaMKII was specifically deleted from the presynaptic side of the CA3-CA1 hippocampal synapse. Conditional CA3 ␣-CaMKII knockou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
72
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(76 citation statements)
references
References 43 publications
4
72
0
Order By: Relevance
“…Therefore, the antidepressant-induced change in aCaM kinase II phosphorylation seems to be a crucial event in the molecular modifications leading to modulation of glutamate release. Indeed, aCaM kinase II has been proposed to regulate probability of release in central synapses during high-frequency presynaptic stimulation (Hinds et al, 2003); the drug-induced molecular and functional changes we found related to aCaM kinase II are in line with this role for the enzyme. The mechanism whereby antidepressants may induce the adaptive changes we observed in aCaM kinase II is at present unknown.…”
Section: Functional Changes Induced By Antidepressants In the Presynasupporting
confidence: 75%
“…Therefore, the antidepressant-induced change in aCaM kinase II phosphorylation seems to be a crucial event in the molecular modifications leading to modulation of glutamate release. Indeed, aCaM kinase II has been proposed to regulate probability of release in central synapses during high-frequency presynaptic stimulation (Hinds et al, 2003); the drug-induced molecular and functional changes we found related to aCaM kinase II are in line with this role for the enzyme. The mechanism whereby antidepressants may induce the adaptive changes we observed in aCaM kinase II is at present unknown.…”
Section: Functional Changes Induced By Antidepressants In the Presynasupporting
confidence: 75%
“…5, available at www.jneurosci.org as supplemental material). The second mechanism appears most likely given previous studies (Llinás et al, 1985;Sakaba and Neher, 2001;Thiagarajan et al, 2002;Hinds et al, 2003;Dick et al, 2008), but the third mechanism cannot be excluded with the data up to now. Thus, to test the third mechanism, we performed two complementary sets of experiments (Fig.…”
Section: Short-term Synaptic Plasticitymentioning
confidence: 59%
“…The majority of neurotransmitter release is triggered by Ca 2ϩ binding to synaptotagmin (Fernández-Chacó n et al, 2001;Maximov and Südhof, 2005), but CaM may function as an ancillary Ca 2ϩ sensor for the asynchronous component of release, which is not mediated by synaptotagmin (Sun et al, 2007). Moreover, CaM may regulate the refilling of the readily-releasable pool (RRP) of vesicles (Sakaba and Neher, 2001) and/or modulate presynaptic release by activating calmodulin-dependent kinase-II␣ (CaMKII␣) and CaMKII␤ (Llinás et al, 1985;Thiagarajan et al, 2002;Hinds et al, 2003;Dick et al, 2008). Finally, CaM controls presynaptic and postsynaptic Ca 2ϩ -channel function (Lee et al, 2000;Dick et al, 2008), mediates postsynaptic long-term plasticity by activating CaMKII␣ and calcineurin (Lisman et al, 2002;Xia and Storm, 2005), and alters neuronal gene expression (Greer and Greenberg, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A possible explanation for the enhancement in learning seen on day 2 under the CAMKII inhibitor may be educed from experiments showing that CAMKII serves as an inhibitory constraint on hippocampal neurotransmitter release during high frequency presynaptic activity (Hinds et al, 2003). As KN-62 did not have any effect in sedentary controls, the effect of exercise on the synapse may be specifically related to the CAMKII system.…”
Section: The Role Of Camkii In Mediating the Exercise-induced Enhancementioning
confidence: 99%